The Site of Disintegration of a Chitosan-coated Capsule - TOMONAGA, Akihito; MINEMURA, Tsuyoshi; NUKUI, Kazuki (Chōnai saikingaku zasshi, 2012)
A chitosan-coated capsule was developed with the aim of delivering bifidobacteria directly to the large intestine, where the bacteria naturally inhabit, by protecting them from gastric acid. A capsule dissolution experiment was conducted using beta carotene as the content; the capsules were first immersed in Solution I, which simulated gastric juice, and slight dissolution was confirmed after 60 minutes. Then they were immersed Solution II which simulated the environment of the small intestine, and a dissolution rate of approximately 3% was confirmed during immersion for 120 minutes. Finally, they were immersed in a pH 3.5 solution to see whether there was any change in the solubility of the chitosan film, and a dissolution rate close to 100% was reached within 60 minutes. These results showed that the capsule was likely to disintegrate in the large intestine as intended. With this finding, an experiment was conducted to confirm the region in the human digestive system where the capsule disintegrates. For this experiment, the capsules were filled with barium sulfate and coated with chitosan and acid-resistant films. In one subject, the capsule remained in the duodenum, and disintegration was not confirmed during the observation period. This may have been due to the capsule remaining in the stomach and the duodenum for a long time for unknown reasons. In the remaining five subjects, the capsule disintegrated in the large or small intestine, and in all of the subjects, it was considered that the capsule started disintegrating between 4.0 and 7.5 hours after ingestion. It was also judged that the capsule completely disintegrated between 5.0 and 8.5 hours after ingestion. Considering how the human digestion system works, these results suggest that the capsule is acid resistant and can reach the large intestine via the small intestine without disintegration. With regard to the case in which the capsule disintegrated in the small intestine, it was believed that the capsule’s retention time in the stomach, as well as in the small intestine, was extended due to the high specific gravity of the capsule, which was filled with barium sulfate, and as a result, it disintegrated in the small intestine due to physical stimuli such as peristalsis. This study showed that the chitosan-coated capsule we developed has disintegration properties different from conventional capsules, is acid resistant and is likely to disintegrate in the large intestine when filled with bifidobacteria.